Agabus abaensis sp. nov., a peculiar species of the confinis-group from central China (Coleoptera: Dytiscidae: Agabinae) - Šťastný, Jaroslav; Hájek, Jiří (Zootaxa, 2016)
Agabus (Acatodes) abaensis sp. nov., from northern Sichuan and south-western Gansu provinces (China) is described and its relevant diagnostic characters are illustrated. The new species is, with some hesitation, classified within the A. confinis species group. Agabus abaensis sp. nov. differs from all species in the group by the combination of the following characters: elytral sculpture with considerably large, distinctly double reticulation in both sexes, and male anterior protarsal claw dentate—the characters resembling some species of the A. arcticus species group. The systematic position of the new species is briefly discussed.